Promising pea varieties for use in the cereal industry in the south of Western Siberia - I. V. Pakhotina; L. V. Omeliyanyuk; E. Yu. Ignatieva; A. A. Asanov; L. T. Soldatova (Зерновое хозяйство России)
The current study was carried out on 20 pea varieties and lines of various origins with a leafless type in the southern forest-steppe of Western Siberia in 2019–2022. The purpose of the study was to conduct a comparative analysis of varieties and breeding lines of domestic and foreign breeding and identify those suitable for processing into cereals. The trial was laid in the nursery of ecological variety testing according to the generally accepted methodology. The technological quality of grain was estimated according to the method of the State Commission for Variety Testing. Weather conditions were contrasting with periods of severe drought. The most favorable years for the formation of a large productivity of pea seeds (5.11 and 5.01 t/ha, respectively) were 2019 (HTC = 0.99) and 2020 (HTC = 0.60). In 2022 (HTC = 1.04), the lowest yield was obtained on average for the trial (2.22 t/ha, environmental index was 1.78), but with an increased proportion of protein (23.86 %, environmental index was +1,07). The variety ‘Yamalsky’ (2.79–5.61 t/ha) was the best in productivity, yielding to foreign varieties in the formation of protein in seeds (21.7 %). High-protein varieties were ‘Bonus 2’ and ‘L 36/18’ (22.7–26.8 %). There has been established that the highest protein percentage is synthesized at a yield level of 3.8 to 4.3 t/ha. There has been clarified correlation between protein yield per unit of area and productivity (r = 0.92) and protein percentage in seeds (r = 0.50). The correlation between 1000- seed weight and their uniformity was close to functional (r = 0.93), and with the total yield of cereals it was medium negative (r = –0.45), with the yield of shelled peas with undivided cotyledons it was strong negative (r = –0.76). The smallest yield of cereals was obtained from peas with a high percentage of coarse fraction (7.0–6.5 mm). In order to produce cereals with a standardized yield and quality, there have been recommended the variety ‘Blagovest’ and the line ‘L 182/15’. There has been established that among high-yielding varieties (4.27–4.63 t/ha) for the cereal industry there can be used such varieties as ‘Yamalsky’, ‘Krasnoufimsky 11’, ‘Aksaysky usatiy 55’, ‘Salamanka’ with a lower yield of shelled peas with undivided cotyledons (49.9–61, 1 %).